A Composite Method of Marine Shafting's Fault Diagnosis by Ship Hull Vibrations Based on EEMD. (30th March 2022) - Wen, Xiaofei; Meng, Wenjie; Sun, Xiaoxiao; Zhou, Ruiping
Abstract : The fault diagnosis is always a key issue in the security field of marine propulsion system. There are obvious problems like the unsteady working of sensors, distortion of original data, and ambivalent feature information from marine shafting's vibration or motion. It is therefore critical to develop a more effective method to identify the fault information so that the safety of marine propulsion system can be pre-estimated. Hence, a composite method which is based on the ensemble empirical mode decomposition (EEMD) and coupled with the autocorrelation method (AM), the fast Fourier transform (FFT), is mixed and applied to identify the fault information of marine shafting during its operating by hull vibration. The contrastive analysis of the three methods and fault feature study are then conducted to assess the effectiveness of the proposed method thoroughly and validated by the author previously. The research indicates that the composite method is available to fault diagnosis of marine shafting by hull vibration which coupled the shafting vibration with fault feature.